GAMBARAN HASIL UJI SARING HEPATITIS B METODE CHEMILUMINESCENCE IMMUNOASSAY (CHLIA) PADA DARAH DONOR DI UDD PMI KABUPATEN BANYUMAS TAHUN 2022 - Alfianni, Sherliana; Mumpuni, Nurpuji; Suhada, Reza Iqbal (Jurnal Analis Kesehatan Kendari, 2023)
ABSTRACT Background: Hepatitis B is a liver infection caused by the Hepatitis B Virus (VHB) which can lead chronic infection and liver cancer, making it at high risk of death. The prevalence of Hepatitis B in 2022 at UDD PMI Banyumas Regency was recorded at 141 donors with a percentage of 0.21% declared Reactive (R) to Hepatitis B from a total of 68,380 donors. UDD PMI Banyumas Regency has been certified CPOB (Good Manufacturing Practices) since 2019 and is headed by doctor Winda Astuti Taruno. Objective: To determine the description of the results of the Hepatitis B screening test with the Chemiluminescence ImmunoAssay (ChLIA) method at UDD PMI Banyumas Regency in 2022. Method: This study is a quantitative descriptive study with a retrospective time approach, namely the results of the Hepatitis B screening test identified with blood donor characteristics, such as gender, age and blood type in UDD PMI Banyumas Regency in 2022. Results: The number of blood carried out by Hepatitis B screening tests during 2022 was 68,380 blood samples, the most samples were in March at 6,387 (9.30%) and the least in May at 4,853 (7.10%). The results of the Hepatitis B screening test obtained Reactive results against Hepatitis B as much as 141 (0.21%) and Non-Reactive as much as 68,239 (99.79%). Based on the characteristics of donors, the results of the Reactive Hepatitis B (R) screening test in donor blood are more common in women, namely 46 donors (0.24%), in the age group (36-45 years) as many as 50 donors (0.31%), in blood type O as many as 53 (0.20%), and in Rhesus positive as many as 141 (0.21%). The handling of reactive blood in UDD PMI Regency is to conduct a duplex examination, if the results are obtained Reactive (Repeated Reactive), then the blood is destroyed and the donor is referred to an Internal Medicine Specialist at the Hospital for re-examination and counseling for the continuation of the donor. Conclusions: The results of the Hepatitis B screening test on donor blood at UDD PMI Banyumas Regency in 2022 were Reactive Hepatitis B of 0.21% and Non-Reactive Hepatitis B of 99.79%. Reactive Hepatitis B is most common in women, in late adulthood and in blood type O. Reactive blood management is in accordance with the Minister of Health Regulation Number 91 of 2015. Keywords: Hepatitis B; ChLIA method; Blood Donor, UDD PMI Banyumas Regency; 2022 ABSTRAK Pendahuluan: Hepatitis B ialah infeksi hati yang disebabkan oleh Virus Hepatitis B (VHB) yang dapat mengakibatkan infeksi kronis serta kanker hati, sehingga beresiko tinggi terhadap kematian. Prevalensi Hepatitis B pada tahun 2022 di UDD PMI Kabupaten Banyumas tercatat sebanyak 141 pendonor dengan persentase 0,21% dinyatakan Reaktif (R) terhadap Hepatitis B dari total pendonor sebanyak 68.380. UDD PMI Kabupaten Banyumas sudah tersertifikasi CPOB (Cara Pembuatan Obat yang Baik) sejak tahun 2019 dan dikepalai oleh dr. Winda Astuti Taruno. Tujuan: Untuk mengetahui gambaran hasil uji saring Hepatitis B dengan metode Chemiluminescence ImmunoAssay (ChLIA) di UDD PMI Kabupaten Banyumas Tahun 2022. Metode: Penelitian ini merupakan penelitian deskriptif kuantitatif dengan pendekatan waktu retrospektif, yaitu hasil uji saring Hepatitis B yang dikaitkan dengan karakteristik pendonor darah, seperti Jenis kelamin, usia dan golongan darah di UDD PMI Kabupaten Banyumas tahun 2022. Hasil: Jumlah darah yang dilakukan uji saring Hepatitis B selama tahun 2022 didapatkan sebanyak 68.380 sampel darah. Hasil uji saring Hepatitis B menunjukkan hasil Reaktif (R) terhadap Hepatitis B sebanyak 141 (0,21%) dan Non Reaktif (NR) sebanyak 68.239 (99,79%). Berdasarkan karakteristik pendonor hasil uji saring Hepatitis B Reaktif (R) pada darah donor lebih sering terjadi pada jenis kelamin perempuan yakni 46 pendonor (0,24%), pada kelompok usia (36 – 45 tahun) sebanyak 50 pendonor (0,31%), pada golongan darah O sebanyak 53 (0,20%), dan pada Rhesus positif sebanyak 141 (0,21%). Penanganan darah reaktif di UDD PMI Kabupaten yaitu melakukan pemeriksaan secara duplo, jika didapatkan hasil Reaktif (Repeated Reactive), maka darah dimusnahkan dan pendonor dirujuk ke Dokter Spesialis Penyakit Dalam di Rumah Sakit untuk dilakukan pengecekkan ulang dan konseling untuk kelanjutan donornya. Kesimpulan: Hasil uji saring Hepatitis B pada darah donor di UDD PMI Kabupaten Banyumas tahun 2022 yang Reaktif Hepatitis B sebesar 0,21% dan Non Reaktif Hepatitis B sebesar 99,79%. Reaktif Hepatitis B paling banyak pada perempuan, pada usia dewasa akhir dan pada golongan darah O. Penanganan darah Reaktif sudah sesuai Peraturan Menteri Kesehatan Nomor 91 Tahun 2015. Kata Kunci: Hepatitis B; Metode ChLIA; Darah Donor, UDD PMI Kabupaten Banyumas; 2022